2020
DOI: 10.1088/1758-5090/ab6f0d
|View full text |Cite
|
Sign up to set email alerts
|

Assessment methodologies for extrusion-based bioink printability

Abstract: Extrusion-based bioprinting is one of the leading manufacturing techniques for tissue engineering and regenerative medicine. Its primary limitation is the lack of materials, known as bioinks, which are suitable for the bioprinting process. The degree to which a bioink is suitable for bioprinting has been described as its "printability." However, a lack of clarity surrounding the methodologies used to evaluate a bioink's printability, as well as the usage of the term itself, have hindered the field. This articl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
221
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 272 publications
(222 citation statements)
references
References 93 publications
1
221
0
Order By: Relevance
“…Considering the latter prior to preparation of the bioink formulation herein, a literature search revealed several recent studies, in which the authors demonstrated remarkable printability of nanocellulose/alginate derived hydrogels, which led to formation of biologically relevant 3D architectures, owing to their highly viscous and shear thinning nature [18,28]. Careful observation of Figure 2 further reveals that at a low shear rate (10 s −1 ), a higher viscosity is observed (viscosity value around 40 Pa s), whereas an increase in the shear rate to 500 s −1 , results in sharply decreased viscosities around 1 Pa s. Our results are also in agreement with previous studies, like the one by Gillispie et al, which further claim that the extrudability can be further assessed using the Live/Dead assay (which will be discussed latter on in the article) [43].…”
Section: Printability Of the Prepared Bioink Formulationsupporting
confidence: 93%
“…Considering the latter prior to preparation of the bioink formulation herein, a literature search revealed several recent studies, in which the authors demonstrated remarkable printability of nanocellulose/alginate derived hydrogels, which led to formation of biologically relevant 3D architectures, owing to their highly viscous and shear thinning nature [18,28]. Careful observation of Figure 2 further reveals that at a low shear rate (10 s −1 ), a higher viscosity is observed (viscosity value around 40 Pa s), whereas an increase in the shear rate to 500 s −1 , results in sharply decreased viscosities around 1 Pa s. Our results are also in agreement with previous studies, like the one by Gillispie et al, which further claim that the extrudability can be further assessed using the Live/Dead assay (which will be discussed latter on in the article) [43].…”
Section: Printability Of the Prepared Bioink Formulationsupporting
confidence: 93%
“…Inks with living cells encapsulated, termed bioink, are in conflict as the characteristics that make a stable print, like density or viscosity, are often in direct contrast to sustaining life, as cells need a porous, compliable environment to grow and migrate [ 24 ]. Rheological requirements of the bioink vary based on the modality of the bioprinting, i.e., droplet-based or inkjet, laser-based, or extrusion-based printing, with the latter being the most common bioprinting method [ 20 , 24 , 25 , 26 ]. Inkjet bioprinting lays a continuous stream of small sized droplets to form the 3D structure.…”
Section: Bioink Requirementsmentioning
confidence: 99%
“…However, this process is usually time consuming and not efficient for large (clinical)-scale tissue manufacturing [ 22 ]. Laser-based bioprinting uses a precise laser beam to solidify the construct within a basin of bioink, but may damage the cells with heat [ 26 ] and is relatively slow [ 25 ]. Extrusion-based bioprinting has a morphology of a filament or string of low viscosity during the print which solidifies once on the print surface holds its shape and supports layering [ 22 ].…”
Section: Bioink Requirementsmentioning
confidence: 99%
“…12 Among them, extrusion-based 3D bioprinting has been the most preferred one due to its ease of use, compatible with a great variety of cells, wide adoption of already established materials, precision manipulation of bioinks, and flexibility printing of complex geometries. [13][14][15][16] During this bioprinting process, it extrudes inks to form continuous building blocks for fabricating constructs, which requires a delicate balance between ink solidification rates and deposition rates so that achieving intricate structures and excellent performance. The preventing printed material from changing shape after placement is a critical challenge that can affect extrusionbased 3D printing.…”
Section: Introductionmentioning
confidence: 99%